Military Government and Development in Northern Nigeria: A Case Study of Katsina City, 1969–1999 - Wycliff, Samuel; Obajobi, Juliet Jenebu (NIU Journal of Social Sciences, 2025)
The Nigerian military, whose central role was to defend the country against external aggression, and national security issues was found in the national politics, governance, and shadow of development from 1966 to 1999. The paper argued that though military government and its rules had been criticized by civilian administration across the globe, in Katsina city the case was different owing to designed programs that earned them the support of the people to the extent that the city experienced tremendous development and transformation beyond what was obtainable in the colonial era and even during the civilian administration of Nigeria’s First and Second Republic. Furthermore, the emergence of the military government on July 29, 1966, led to the transformation of Katsina City from an administrative division to an area council in 1969, then to a Local Government Area (LGA) in 1976, and then to a Katsina State Capital City following 1987 state creation. Thus, all these phases of transformation led to a series of developments ranging from civil servant deployment and recruitment opportunities to the provision of healthcare facilities, electricity, and water; educational advancement; security of the city; construction of roads and markets, which attract lots of fortune seekers; and migration of Nigerian communities, which boosted the cosmopolitan nature of the city.  To this end, through quantitative and historical research methodologies, coupled with functionalism theory and the aid of primary and secondary data, this paper examines the role of military government in the political and socio-economic development and transformation of Katsina City from 1969 to 1999.               Keywords:   Military Government, Development, Katsina City, Political, Socio-economic.